Pavlovian Extinction and Recovery Effects in Aversive Pavlovian to Instrumental Transfer - Campese, Vincent D.; Kim, Ian T.; Rojas, Gerardo; LeDoux, Joseph E. (Frontiers in Behavioral Neuroscience, 2017)
Three studies explored the sensitivity of aversive Pavlovian to instrumental transfer (PIT) to Pavlovian extinction in rodents. Rats underwent Pavlovian conditioning prior to avoidance training. The PIT test then involved assessment of the effects of the Pavlovian conditioned stimulus (CS) on the performance of the avoidance response (AR). Conducting extinction prior to avoidance training and transfer testing, allowed spontaneous recovery and shock reinstatement of extinguished motivation, whereas conducting extinction following avoidance training and just prior to PIT testing successfully reduced transfer effects. This was also the case in a design that compared responding to an extinguished CS against a non-extinguished CS rather than comparing extinguished and non-extinguished groups to one another. While extinction treatments in many appetitive PIT studies do not successfully reduce transfer, and can sometimes enhance the effect, the current findings show that an extinction treatment temporally close to transfer testing can reduce the motivational impact of the aversive Pavlovian CS on instrumental avoidance responding.